COVID-19: Are School Counseling Services Ready? Students' Psychological Symptoms, School Counselors' Views, and Solutions - Karaman, Mehmet Akif; Eşici, Hasan; Tomar, İsmail Hakkı and Aliyev, Ramin (Frontiers in Psychology, 2021)
The purpose of the current study was to investigate the effects of COVID-19 on high school students’ psychological symptoms and to understand how ready counselors and school counseling services are. Therefore, this research is designed under two different studies: A) Study 1: Effects of COVID-19 pandemic on students’ psychological symptoms and B) Study 2: Views and expectations of students and school counselors about school counseling services. The first study was a quantitative study and included 549 high school students (398 females, 151 males). A Structural Equation Model (SEM) was created to examine the effects of COVID-19 pandemic on participants’ psychological symptoms. The Impact of Event Scale-Revised (IES-R) scores showed that 107 (19.50%) individuals had a score of 50 and above pointing out that individuals in this group had severe impact of event/ trauma symptomologies. The SEM analysis indicated that IES-R scores had a total effect of .79 on anxiety, .75 on depression, .74 on negative self-concept, .68 on somatization, and .66 on hostility scores. Furthermore, female students had significantly higher scores on anxiety, depression, negative self-concept, somatization, hostility, and impact of events variables than male students. Study 2 was a qualitative design and consisted of five school counselors and five students from different schools. The results indicated that students' difficulties during the COVID-19 outbreak were educational, cognitive, emotional, physiological, relational, technological and related to routines. Academic, social, emotional and behavioral issues came to the fore among the difficulties that can be experienced if students start face-to-face education. On the other hand, the school counselors listed that family relations, personal-social, emotional and academic themes were the difficulties experienced by the students at the beginning of the COVID-19. In addition, when COVID-19 started, the services offered by school counselors were discussed under: 1) services for the student, 2) services for the family, and 3) services for the teacher. Finally, according to the opinions of the school counselors, if students start face-to-face education, they may experience emotional, academic and relational difficulties. In summary, it is vital that student personality services be prepared and implemented by school counseling services for schools based on results.